2018
DOI: 10.1016/j.jmii.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The incidence rate, trend and microbiological aetiology of prosthetic joint infection after total knee arthroplasty: A 13 years’ experience from a tertiary medical center in Taiwan

Abstract: The results showed that the risk of post-TKA prosthetic joint infection is decreasing. Microbiology results showed that early-onset post-TKA prosthetic joint infection is associated with a higher risk of gram-negative bacterial infection. Physicians should be aware of this risk in order to correctly select empirical agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…We also found that MDR nonfermenters and MDR S. aureus rates were higher at tropical sites vs. subtropical. Reported cases of MDR nonfermenters in the orthopaedic literature are too low to be comparable; however, we note that our rates of MDR S. aureus are consistent with other studies [20,21,[23][24][25][26]. In their assessment of pathogens cultured from surgical site infections following joint arthroplasty and spinal fusions, Norton et al found that 33% of S. aureus was methicillin-resistant and similarly, Dudareva et al identified that 22.5% of S. aureus species cultured from chronic osteomyelitis patients in the United Kingdom were MDR [20,24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that MDR nonfermenters and MDR S. aureus rates were higher at tropical sites vs. subtropical. Reported cases of MDR nonfermenters in the orthopaedic literature are too low to be comparable; however, we note that our rates of MDR S. aureus are consistent with other studies [20,21,[23][24][25][26]. In their assessment of pathogens cultured from surgical site infections following joint arthroplasty and spinal fusions, Norton et al found that 33% of S. aureus was methicillin-resistant and similarly, Dudareva et al identified that 22.5% of S. aureus species cultured from chronic osteomyelitis patients in the United Kingdom were MDR [20,24].…”
Section: Discussionsupporting
confidence: 91%
“…In their cohort of orthopaedic trauma patients in Brazil, Tuon [20][21][22]. In Taiwan, Wang et al also identified lower rates of P. aeruginosa, which made up just 2.8% of pathogens causing prosthetic joint infection [23]. Though the mechanisms are unclear, in our study, the higher frequency of nonfermenters identified at tropical vs. sub-tropical sites likely reflects a predilection of these pathogens for included regions, and the complexity of niches may mean that, even within tropical environments, there are regions of varying suitability for these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…There are several useful classifications of PJI in different categories, namely based on the mode of acquisition and/or time from prosthesis implantation, but none of them are universally accepted [8,16]. A good deal of what is currently known about the microbial etiology of different categories of PJI is based on studies that are limited by small sample sizes [11,15,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31] and describe single-center experiences [12,15,17,18,19,20,21,22,23,24,26,27,28,30,31,32]. Most focus on specific types of infection, [11,21,23,25,29] surgical strategies used during treatment [22,31], or include only infections occurring within a limited period of time after prosthesis implantation [30,33].…”
Section: Introductionmentioning
confidence: 99%
“…Although international efforts to minimize the risk of these infections are ongoing, PJIs continue to develop in alarming numbers. Current estimates of the rate of PJI range between 0.5% and 2.4% of primary hip and knee arthroplasties [7], and PJI can complicate up to 20% of revision arthroplasties [8,9]. Some authors have suggested that these numbers for primary total joint arthroplasty are both underestimated and increasing [10].…”
Section: Introductionmentioning
confidence: 99%